The Role Of Extracurricular Activities In Developing Students' Interests And Talents In Elementary Schools - Sofyan Iskandar; Primanita Sholihah Rosmana; Alifia Nur Azizah H.A; Ayang Ranisa Rahma; Nurfenti Widiya Nengsih; Tiominar Febrianti Puspita Sari (PT. Anagata Sembagi Education, 2024)
Elementary school is a level of education that can shape students' personalities and develop the potential embedded within themselves. Apart from delivering academic material, there is also a need for other school programs to support student growth and development, one of which is extracurricular activities. Extracurricular activities are an integral part of school life that can provide various benefits for students. knowledgeable and character. To achieve optimal educational goals, there needs to be supporting factors from various parties, one of which is the role of teachers in schools to develop creativity, interests and talents. This research uses a literature study method by looking for theoretical references and written summaries such as from books, journals or e-books by organizing or integrating them into the necessary topics. Participating in extracurricular activities is one way for students to explore their interests and talents. Students' potential and abilities can be seen by participating in these activities. By knowing one's talents, interests and potential, it will be easier for a person to determine steps in achieving more focused life goals.